(untitled) (EUROPEAN AND ASIAN LAW REVIEW, 2024)
This publication asks whether procedures for collective bargaining or collective agreement conclusion constituting alternatives to those specified in applicable labour legislation are possible, including in cases where the employees designate their own representatives to participate in these processes. The author believes that in a situation where the result of collective bargaining in any form proposed by the parties is a legitimate and inherently adequate collective agreement concluded in the interests of the concerned employees featuring local norms of a material nature that improve the situation of said employees in comparison with the working conditions established by applicable laws, other regulations and/or agreements, the right to alternative means of collective bargaining, just as the choice of any method of representing their interests in this process, should be permitted by law. The corresponding amendments to the provisions of labour legislation are proposed.